Meta-Analisis : Penerapan Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar Siswa - Uki, Nonci Melinda; Sudiatmika, AAIA Rai; Suma, I Ketut; Suardana, I Nyoman (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This research aims to analyze the effectiveness of the Project Based Learning (PjBL) learning model in improving student learning outcomes at the elementary, middle and high school levels. The research method used is meta-analysis by re-analyzing articles from 19 research results that have been published, and can be accessed online, which were published in 2014-2023. The results of this meta-analysis research show that the effect size value at the high school level is 1,350, at the elementary school level is 2,636, and at the junior high school level is 4,727. From the effect size analysis, it can be concluded that the implementation of the PjBL learning model has proven effective in improving student learning outcomes at the elementary, middle and high school levels.